Barriers to accessing and receiving mental health care for paid and unpaid carers of older adults - Clarissa Giebel; Laura Prato; Sue Metcalfe; Hazel Barrow (Wiley, 2024)
Abstract Aim The aim of this qualitative study was to explore the barriers and facilitators to accessing and receiving mental health care for paid and unpaid carers of older adults. Methods Unpaid and paid carers for older adults in England were interviewed remotely between May and December 2022. Participants were asked about their experiences of mental health needs and support. Reflexive thematic analysis was used to analyse the data. Results Thirty‐seven carers participated (npaid = 9; nunpaid = 28), with the majority caring for a parent with dementia. Thematic analysis generated four themes: lack of healthcare support, social care system failing to enable time off, personal barriers and unsupportive work culture. Healthcare professionals failed to provide any link to mental health services, including when a dementia diagnosis was received. Structural and organisational barriers were evidenced by carers being unable to take time off from their unpaid caring duties or paid caring role, due to an absence of social care support for their relative. Conclusions This is the first study to have explored the barriers to mental health care and support for paid and unpaid carers for older adults and suggests that structural, organisational and personal barriers cause severe difficulties in accessing required support to care for older relatives, services users and residents. Public Involvement Two unpaid carers aided with the development of topic guides, data analysis, interpretation and dissemination. Both were supported and trained to code anonymised transcripts.